He didn't protest either - :::Creator::::::::::::; :::Contributor::::::::::::; :::Editor::::::::::::; University of California, Berkeley:::University place::::::::::::
Silk screen print of a steer sectioned off into meat parts. The words "He didn't" appear above the steer and "protest either" appear below.